Online screening for excessive daytime sleepiness: a feasibility study - Hlodak, Jan; Geckova, Andrea Madarasova; Carnakovic, Simona; Feketeova, Eva (Frontiers in Psychology, 2024)
Purpose: Excessive daytime sleepiness (EDS) can have a significant impact on health and quality of life but may remain undiagnosed due to low awareness and underestimation of the clinical impact of the symptoms. An online screening tool supported by media campaigns might increase awareness and help detect undiagnosed cases of EDS and narcolepsy. The aim of this study was to develop an online screening method, along with a media campaign focusing on EDS, and evaluate its feasibility.Methods: Online screening supported by a media campaign targeting young and middle-aged adults (18-45 years old) were developed and implemented over a period of one year starting from November 2022. The Epworth Sleepiness Scale was used to identify EDS, and the Swiss Narcolepsy Scale was used to identify narcolepsy. In addition, the data on sociodemographic characteristics, selected sleep and health indicators and lifestyle behaviors were collected to indicate the etiology of the EDS. Feasibility, e.g., implementation and practicality, was assessed by the response rate, response to the promotion strategy, time spent on the tool, sample characteristics, and the prevalence of identified EDS and narcolepsy cases.Results: A total of 2,390 people opened the screening link; 568 of them completed the online screening (23.8%), and most of them (n=437, 76.9%) left their contact data to receive feedback.We identified 171 (30.1%) respondents at risk of EDS and 61 (10.7%) at risk of narcolepsy. The mean time of the screening was 15 minutes.An online screening tool supported with a campaign seems to be a feasible way to increase awareness about EDS and prevent delayed detection of EDS cases.